PENGARUH PROMOSI PENJUALAN DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA E-COMMERCE SHOPEE DI DKI-JAKARTA) - Fauzan Akhyar (2022)
This thesis aims to examine the effect of sales promotion and service quality on consumer purchasing decisions in e-commerce Shopee. This study uses a quantitative method using SmartPLS. The number of samples in this study were 100 respondents. Respondent requirements in this study are Shopee users with a minimum of 2 shopping times. Determination of the sample using purposive sampling technique by setting the criteria first. Data collection techniques by giving questionnaires to respondents. In proving and analyzing this, validity and reliability tests, R-Square tests, Q-Square tests, and the effect coefficient values are used by the original sample through the path analysis test (path coefficient) and finally through the t-statistic test. Through testing the validity and reliability of the data it can be said to be valid and reliable. Based on the results of the Q-Square test stated that the model has a relevant predictive value. The results of the data analysis showed that the sales promotion variable had a negative and insignificant -0.076 effect, while the service quality variable had a positive and significant effect of -0.721 on purchasing decisions. The R square results in this study show that the contribution of the sales promotion and service quality variables together is 52.90% while the remaining 47.10% is influenced by other variables outside this research model, such as price, shopping experience, customer trust, brand image, and so forth.